Hybrid Maritime Warfare: Building Baltic Resilience. Issue 1 (2nd January 2017) - Schaub, Gary; Murphy, Martin; Hoffman, Frank G
Abstract : Russia's use of hybrid warfare techniques has raised concerns about the security of the Baltic States. Gary Schaub, Jr, Martin Murphy and Frank G Hoffman recommend a series of measures to augment NATO's Readiness Action Plan in the Baltic region, including increasing the breadth and depth of naval exercises, and improving maritime domain awareness through cooperative programmes. They also suggest unilateral and cooperative measures to develop a sound strategic communications strategy to counter Moscow's information operations, reduce dependence on Russian energy supplies and build the resilience of critical undersea and maritime infrastructure. Finally, the article proposes that more attention be devoted to resolving unsettled maritime boundaries between Latvia and Lithuania, and between Denmark and Poland, to reduce the chance that these can be exploited to increase regional instability as part of a larger hybrid campaign.